2013
DOI: 10.1200/jco.2012.46.3323
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Treatment Transformed: A Population-Based Study of Changes in Initial Management Approaches in the United States

Abstract: Initial treatment for multiple myeloma has changed markedly. Most patients now receive novel agents, with a decline in the use of traditional chemotherapy. Use of transplantation and novel agents varies with race and insurance. These findings document rapid changes in patterns of care and highlight addressable disparities in myeloma care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 21 publications
(9 reference statements)
2
69
0
Order By: Relevance
“…Prior studies have demonstrated that Medicaid recipients of all ages are less likely to obtain recommended care compared with those who are privately insured. [5][6][7] Medicare patients who do not have Medicaid or supplemental private insurance face significant out-of-pocket expenses. Medicare patients with no supplemental insurance have been reported to receive less cancer treatment.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Prior studies have demonstrated that Medicaid recipients of all ages are less likely to obtain recommended care compared with those who are privately insured. [5][6][7] Medicare patients who do not have Medicaid or supplemental private insurance face significant out-of-pocket expenses. Medicare patients with no supplemental insurance have been reported to receive less cancer treatment.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Interviewees cited a wide range of risk stratification strategies, although academic physicians identified cytogenetic testing as the most valuable risk assessment tool, followed by the formal International Myeloma Working Group or nccn risk stratification criteria 22 . Only 1 community physician reported using risk stratification in his practice-indeed, the predominant approach to determining transplantation referral and induction therapy for newly diagnosed patients in the community was informal.…”
Section: Risk Stratification and Induction Therapymentioning
confidence: 99%
“…Notably, new guidelines from the International Myeloma Working Group and the U.S. National Comprehensive Cancer Network (nccn) recommend the use of risk assessment and risk-adapted treatment of mm 14,15,[18][19][20] . However, population-and practice-level data about initial mm treatment patterns point to considerable variability in practice 21,22 . The underlying drivers of that variation remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, new therapeutic agents have been incorporated into the treatment algorithm for patients with MM, increasing their survival rates. [1][2][3] Further research into new treatments for MM is essential in order to improve the survival of patients. One potential target for MM therapy is the hepatocyte growth factor (HGF)/mesenchymal-epithelial transition (MET) axis.…”
mentioning
confidence: 99%